Conhecimento prático profissional e prático pessoal: experiências que vivi/vivo são as histórias que me constituem professor - Oliveira, Gabriel Silva de (2017)
In this research based on the theoretical-methodological constructs of Narrative Inquiry (CLANDININ, CONNELLY, 2000, 2011, 2015, CONNELLY, CLANDININ, 2004), I sought to understand some of my life experiences and their possible implications in my teaching education. Thus, besides being the researcher, I was the only direct research participant. My initial inquiries were: (i) how do the teaching stories I lived/live build my understanding of the teaching profession? (ii) how does other people's understanding of being a teacher interrupt my teaching story/stories? To compose my field texts, I chose to focus on the experiences that I have lived before and after my undergraduate degree in Languages, so that my stories as an undergraduate student were not contemplated. The context of my research was the public school where I have worked since August 2015. The school is located in Monte Alegre de Minas - Minas Gerais State, and my field texts were interpreted through the Meaning Composition perspective (ELY; VINZ; ANZUL; DOWNING, 2001). The theoretical basis for this research were the concepts of personal and practical professional knowledge (CLANDININ, CONNELLY, 1995) and stories to live by (CONNELLY, CLANDININ, 1999). I also discussed the concepts of interrupted stories (MURPHY, 2004) and liminality (HEILBRUN, 1999; LUNDBERG, 2000). As I relived my experiences, I discussed not only my own conceptions of being a teacher, but also the understanding that other people seem to have about the teaching profession. At the end, I understood that throughout the time, my teaching stories were shaping my own conception of being a teacher, so that the experiences that I have lived and have been living are strongly intertwined with my personal practical knowledge and my professional practical knowledge.